Dinitrosyliron complexes are the most abundant nitric oxide-derived cellular adduct: Biological parameters of assembly and disappearance - Hickok, Jason R. (2011)
It is well established that nitric oxide (•NO) reacts with cellular iron and thiols to form dinitrosyliron complexes (DNIC). Little is known, however, regarding their formation and biological fate. Our quantitative measurements reveal that cellular concentrations of DNIC are proportionally the largest of all •NO-derived adducts (900 pmol/mg protein (45–90 μM)). Using murine macrophages (RAW 264.7), we measured the amounts, and kinetics of, DNIC assembly and disappearance from endogenous and exogenous sources of •NO in relation to iron and O(2) concentrations. Amounts of DNIC were equal to or greater than measured amounts of chelatable iron and depended on the dose and duration of •NO exposure. DNIC formation paralleled the upregulation of iNOS and occurred at low physiologic •NO concentrations (50–500 nM). Decreasing the O(2) concentration reduced the rate of enzymatic •NO synthesis without affecting the amount of DNIC formed. Temporal measurements revealed that DNIC disappeared in an oxygen-independent manner (t½ = 80 min) and remained detectable long after the •NO source was removed (>24 h). These results demonstrate that DNIC will be formed under all cellular settings of •NO production and that the contribution of DNIC to the multitude of observed effects of •NO must always be considered.